Bibliometric portrait of stress coping research in higher education (2020–2025): global trends, thematic clusters, and research gaps - Mufadhal Barseli; Ifdil Ifdil; Vera Sriwahyuni Nengsih; Nilma Zola; Lira Erwinda; Berru Amalianita; Linda Fitria; Rima Pratiwi Fadli (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aimed to map the development of international research on coping strategies for managing stress among college students by examining publication patterns, thematic structures, and emerging research directions. A bibliometric analysis was conducted using 130 journal articles indexed in Scopus and published between 2020 and 2025. Data were collected following the PRISMA framework and analyzed using VOSviewer and R Studio to visualize keyword networks, thematic clusters, and country contributions. The results revealed a substantial increase in publications since 2020, with the United States and India leading research productivity. Four major research themes were identified: coping and psychological adaptation, academic and psychosocial contexts, mental health consequences, and predictor factors with psychological assessment. Mindfulness, emotional regulation, problem-focused coping, social support, and digital interventions emerged as the most frequently investigated coping approaches. Indonesia showed increasing research activity, although international collaboration and experimental studies remain limited. These findings provide valuable insights into the evolution of research on student stress management and offer directions for developing evidence-based counseling interventions and mental health policies in higher education.